The Potential Effect of Mucuna pruriens Seed Extract on Sperm Quality experimental study on mice exposed to cigarette smoke (Bangladesh Journal of Medical Science, 2021)
Background: Infertility has been more common problems among couple of reproductive age. One of the factors causing this disorder is unhealthy environmental factors including exposure to cigarette smoke. Polynuclear aromatic hydrocarbons (PAHs) in cigarette smoke can cause testicular atrophy, while the free radicals can inhibit the stages of spermatogenesis, and nicotine in cigarettes affects the brain dopamine levels affecting the levels of GnRH, and subsequently affect the levels of FSH and LH needed in spermatogenesis. The use of Mucuna pruriens seed extract containing antioxidants and L-dopa is expected to improve the quality of sperm after exposure to cigarette smoke.Objective: This study aimed to determine the effect of Mucuna pruriens seed extract on the sperm quality in mice exposed to cigarette smoke.Methods: This study was an experimental study with a post test only control group design. A total of 20 mice were divided into 4 groups of five mice each. All groups were exposed to cigarette smoke. Group 1 was the negative control exposed to cigarette smoke. Groups 2, 3, 4 were exposed to cigarettes smoke and given Mucuna pruriens seed extracts at the dose of 250; 300; and 350 mg/Kg BW/day. Parameters of sperm quality included concentration, morphology, motility and viability.Results: Post hoc tests showed there were significant differences among treatment groups.Conclusion: the administration of Mucuna pruriens seed extract affects the sperm quality of BALB/c mice exposed to cigarettes smoke.Bangladesh Journal of Medical Science Vol.20(4) 2021 p.768-773